Typing of Pseudomonas aeruginosa in cystic fibrosis patients - Tomič, Viktorija (Zdravniški vestnik, 2010)
Background: The aim of our study was to determine the genotypes and antimicrobial susceptibility profiles of Pseudomonas aeruginosa isolates of cystic fibrosis (CF) patients. Methods: We included 18 P. aeruginosa isolates from 10 patients treated as in-patients or outpatients at University Clinic ofRespiratory and Allergic Diseases Golnik between 1 January 2006 and 31 December 2008. Results: We determined 8 pulsotypes of P. aeruginosa. Pulsotypes A and C had 4 subtypes each. Different antimicrobial susceptibilitypatterns were observed in isolates with closely related macrorestriction profiles. Conclusions: We conclude that at a given time, patients with CF attending our clinic were colonized or infected with phenotypically and genotypically distinct strains of P. aeruginosa.
Keywords: antibiotic; Antibiotics; Antibiotiki; Cistična fibroza; Classification; Cystic Fibrosis; Fenotip; Genotip; Genotype; Microbial Sensitivity Tests; Mikrobni, občutljivostni testi; Phenotype; Pseudomonas Aeruginosa; tipizacija